THE PHILLIPS CURVE IN A MATCHING MODEL. (13th May 2019) - Hu, Tai‐Wei; Wallace, Neil
Abstract: Following ideas in Hume, monetary shocks are embedded in the Lagos‐Wright model in a new way: There are only nominal shocks accomplished by individual transfers that are sufficiently noisy so that realizations of those transfers do not permit the agents to deduce much about the aggregate realization. Assuming that the distribution of aggregate shocks is almost degenerate, aggregate output increases with the growth rate of the stock of money—our definition of the Phillips curve. This almost degeneracy assumption is far from being necessary; under some mild conditions, the Phillips curve result holds for a large class of distributions.